Aviation industry technological sovereignty optimization problem formulation - I. Y. Bodrova; A. V. Gostev; G. D. Fainburg (Научный вестник МГТУ ГА, 2025)
The aviation industry faces the difficult task of maintaining and further increasing the population air mobility at the present stage of domestic air transport and country economy development. It is fixed in the Comprehensive Program for Russian Federation Aviation Industry Development until 2030 (as amended by Decree of Russian Federation Government No. 1102-r dated May 4, 2024). There is an urgent need to develop and introduce domestic production components into aircraft type design in the context of the cessation of interaction between Russian aviation enterprises and foreign suppliers of goods and services. These actions make it possible to ensure industrial technological sovereignty and further operation of aviation equipment with the required levels of reliability and safety. The article presents a flowchart of this process developed by the authors. The flowchart considers possible types of import substitution of components. The authors performed a comparative analysis of the forecast of fleet retirement and commissioning of newly developed aviation equipment based on the available statistical data on the operation of short-haul aircraft. The need for the development of sectoral corrective measures is shown based on its results. This fact confirms the relevance of the chosen research area. The process of integration of Russian-made components into the aircraft structure is considered from the point of view of program management in the publication. The authors describe the basic principles and methods of prioritizing projects using the example of 10 components. This considers the total budget of the program, as well as its resource intensity. The optimization task is formulated in the publication based on the results of the work performed. This publication is the main one for the further development of an algorithm that will allow solving priority tasks of continued airworthiness of both the fleet in operation and newly developed aircraft.